Strain-induced effects in the electronic and optical properties of Na0.5Bi0.5TiO3: An ab-initio study. (September 2020) - Behara, Santosh; Priyanga, G. Sudha; Thomas, Tiju
Highlights: Strain-induced ground-state properties of Na0.5 Bi0.5 TiO3 -NBT are analyzed for the first time. NBT (unstrained and compressed) have both direct and indirect band gaps. NBT becomes a clearly indirect band gap semiconductor under tension. Optical spectra show red-shift (under tension) and blue-shift (under compression). Results are relevant to usage of NBT for charge separation and charge storage applications. Abstract: The ground-state properties of sodium bismuth titanate (Na0.5 Bi0.5 TiO3 -NBT) are studied using first-principles calculations based on density functional theory (DFT). The electronic band structure reveals that the direct and indirect band gaps are rather close (within ∼0.07 eV of each other). This has implications for resolving the existing variance in reports regarding the nature of band gap in NBT and supports He et al.'s recent experiment-based inference. We also report hydrostatic strain-induced ( ε = -0.02 (compression) to 0.02 (tension)) band gap variation and demonstrate electron/hole effective mass (me */ mh *) tunability in NBT. Importantly in compression, NBT has both direct and indirect band gaps that are rather close; but in tension, it is clearly an indirect band gap system. We identify conditions ( ε = 0, -0.01) wherein me * > mh *; this is known to be for a predictive measure for transparent p -type conducting oxides. For all the optical constants, we find a significant blue-shift in their spectra under compressive strains and a nominal red-shift in their values under tensile strains. Compression is pointed to as a rather facile means to tune the optical properties of NBT. Our results offer pointers that can make NBT relevant for applications involving light-harvesting, charge separation, and charge storage.